Effect of Fresh Citrus Pulp Supplementation on Animal Performance and Meat Quality of Feedlot Steers - Santiago Luzardo; Georgget Banchero; Virginia Ferrari; Facundo Ibáñez; Gonzalo Roig; Valentín Aznárez; Juan Clariget; Alejandro La Manna (Animals, 2021)
The use of fruit by-products such as citrus pulp represents a feeding ingredient that deserves to be evaluated as an energy source in animal rations. Thirty-six British breed steers were allotted to one of the three feeding treatments (12 steers/treatment): 0%, 15% and 30% of fresh citrus pulp inclusion in the ration in a randomized complete block design to evaluate animal performance and carcass and meat quality traits. In the present study, the inclusion of fresh citrus pulp up to 30% of the diet did not affect the animal average daily gain (p > 0.05) but steers that were fed the pulp consumed less feed (p < 0.05) and presented a lower feed conversion ratio (p < 0.05) than their counterparts without citrus pulp in their diet. No effect of fresh citrus pulp was observed on carcass and meat quality (p > 0.05). A greater lipophilic antioxidant capacity (p < 0.05) in meat was observed when fresh citrus pulp was offered at 15% of the diet. Fresh citrus pulp used up to 30% as a feed ingredient in feedlot rations does not negatively affect animal performance or meat quality but, rather, has a positive effect on dry matter intake and a better feed conversion ratio.